PREFERENSI BERTELUR NYAMUK Aedes aegypti L. BERDASARKAN JARAK PENEMPATAN OVITRAP BERMEDIA AIR DOMESTIK TERHADAP OVITRAP BERMEDIA AIR RENDAMAN JERAMI - Wahyu Nur Hidayah; Jafron Wasiq Hidayat; Rully Rahadian (Jurnal Akademika Biologi, 2013)
Ovitrap is one of the environmentally friendly equipment of controlling Aedes aegypti which causes dengue fever. The utilization of ovitraps by adding attractant substances which are placed in certain distances can stimulate the mosquitoes’ sense of smell in order to lure them. The objective of this study were to determine the effective placing distance of ovitrap’s domestic water media on ovitrap’s hay-soaked water medium in order to lure Ae. aegypti on laying eggs, and to understand the oviposition preferences of Ae. aegypti based on the  placing distance of ovitrap’s domestic water media on ovitrap’s hay-soaked water medium. This research design was factorial experiment by using Split Plot. The water medium used was hay-soaked water as the control. The domestic water media used were well water, tap water, and rain water which were placed with the distance of 0 meter, 1 meter, 3 meters, and 5 meters from the hay-soaked water by using 3 replications. The independent variable were the placing distance and water media, while the dependent variable was the number of eggs trapped. The data were analyzed by using two-way ANOVA with the significance level of 95%. The findings showed that the placing of ovitrap’s well water and tap water with the distance of 5 meters is still effective to distract the oviposition preferences of Ae aegypti on hay-soaked water, while in the well water was only effective up to 3 meters. The water media has no effect on oviposition preferences of Ae aegypti when they are placed up to 5 meters away from the hay-soaked water. This happens due to the high concentration of ammonia in the hay-soaked water which attract the mosquitoes to choose compared to other water media to lay eggs.    Keywords: Aedes aegypti, ovitrap, attractant, hay-soaked water, ammonia